A prospective observational study of iron isomaltoside in haemodialysis patients with chronic kidney disease treated for iron deficiency (DINO) - Ashraf I. Mikhail (BMC Nephrology, 2019)
Abstract Background Iron deficiency is frequent in haemodialysis (HD) patients with chronic kidney disease (CKD), and intravenous iron is an established therapy for these patients. This study assessed treatment routine, effectiveness, and safety of iron isomaltoside (IIM) 5% (Diafer®) in a HD cohort. Methods This prospective observational study included 198 HD patients converted from iron sucrose (IS) and treated with IIM according to product label and clinical routine. Data for IIM were compared to historic data for IS in 3-month intervals. The primary endpoint was to show non-inferiority for IIM versus IS in haemoglobin (Hb) maintenance. Results Most patients (> 60%) followed a fixed low-dose iron treatment protocol. Three minutes were required for preparation and administration of IIM. Erythropoiesis-stimulating agent (ESA) was used in > 80% of patients during both IIM and IS phases. The maintenance of Hb was similar with both iron drugs; the mean Hb level was 11 g/dL, and the mean change of 0.3 g/dL (95% confidence interval: 0.1, 0.5) for IIM 0–3 months compared to IS demonstrated non-inferiority. Nine adverse drug reactions were reported in 2% of patients administered IIM. All patients had uneventful recoveries. The frequency of metallic taste was higher with IS compared to IIM (34% versus 0.5%, p < 0.0001). Conclusions IIM is effective and well tolerated by CKD patients on HD. IIM was non-inferior to IS in maintenance of Hb, and had similar ESA requirements. The fast-push injection of IIM may enable logistical benefits in clinical practice, and the low frequency of metallic taste contributes to patient convenience. Trial registration ClinicalTrials.gov identifier NCT02301026, study registered November 25, 2014.